Exposing the trion's fine structure by controlling the carrier concentration in hBN-encapsulated MoS2. Issue 44 (5th November 2021) - Grzeszczyk, Magdalena; Olkowska-Pucko, Katarzyna; Nogajewski, Karol; Watanabe, Kenji; Taniguchi, Takashi; Kossacki, Piotr; Babiński, Adam; Molas, Maciej R.
Abstract : Atomically thin materials, like semiconducting transition metal dichalcogenides, are highly sensitive to the environment. Abstract : Atomically thin materials, like semiconducting transition metal dichalcogenides, are highly sensitive to the environment. This opens up an opportunity to externally control their properties by changing their surroundings. In this work, high-quality van der Waals heterostructures assembled from hBN-encapsulated monolayer MoS2 are studied with the aid of photoluminescence, photoluminescence excitation, and reflectance contrast experiments. We demonstrate that carrier concentration in MoS2 monolayers, arising from charge transfer from impurities in the substrate, can be significantly tuned within one order of magnitude by the modification of the bottom hBN flake thickness. The studied structures, characterized by spectral lines with linewidths approaching the narrow homogeneously broadened limit enabled observations of subtle optical and spin-valley properties of excitonic complexes. Our results allowed us to resolve three optically-active negatively charged excitons in MoS2 monolayers, which are assigned to the intravalley singlet, intervalley singlet, and intervalley triplet states.